TINJAUAN PELAKSANAAN PELEPASAN INFORMASI REKAM MEDIS UNTUK KEPERLUAN VISUM ET REPERTUM DI RUMAH SAKIT X - Emanuel Yanoarius Ngaba; Edih Gunawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to review the implementation of medical record information disclosure for Visum et Repertum purposes at Hospital X. The method used is descriptive with a qualitative approach, employing data collection techniques through observation and interviews with 10 informants, as well as analysis of 78 Visum files during the period January–July 2025. The results of the study indicate that all medical information release procedures were carried out in accordance with operational standards (100%). However, the level of understanding among medical record staff varied: 20% had very good knowledge, 20% had good knowledge, while only 20% had sufficient understanding, and 40% had poor knowledge. Educational background and work experience were the main causes of this disparity. This study concludes that while the release procedures have been carried out properly, improving staff understanding and providing training are essential to ensure medical data security and support valid legal processes.